Medical and psychological support of multiple sclerosis patients: basic principles and objectives - E. L. Nikolaev; T. A. Karavaeva; N. V. Vasilyeva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The work is devoted to the description of the main principles and tasks of medical and psychological support of patients with multiple sclerosis (MS). These principles include: the principle of continuity and phase, the principle of complexity, the principle of accessibility, the principle of differentiation, the principle of integrativity and the principle of system-style. The tasks of medical and psychological support of MS patients are related to period of the disease, key characteristics of the clinical picture and therapeutic problems.